Hubungan Antara Tingkat Spiritualitas dengan Kualitas Hidup Pasien Stroke yang Mengalami Gangguan Mobilitas Fisik - Angelita Hardiyanti Rukmana; Mohammad Arifin Noor; Dwi Retno Sulistyaningsih (NAJ Nursing Applied Journal, 2025)
Stroke is one of the leading causes of disability worldwide and significantly impacts patients' quality of life. Physical mobility impairment can reduce patients' independence, while spirituality potentially enhances coping mechanisms. This study aims to evaluate the relationship between spirituality level and the quality of life of stroke patients with physical mobility impairment at RSI Sultan Agung, Semarang. This study employs a descriptive quantitative design with a correlational approach. A total of 88 respondents were selected through simple random sampling and assessed using the Daily Spiritual Experience Scale (DSES) and WHOQOL-BREF. Results indicate that most respondents have a moderate level of spirituality (44.32%) and good quality of life (31.82%). Spearman correlation analysis shows no significant relationship between spirituality level and quality of life (r = 0.134; p = 0.212). Nevertheless, a holistic approach incorporating physical, psychological, social, and spiritual aspects remains essential for enhancing patient well-being.